POST-EXPOSURE AND PRE-EXPOSURE PROPHYLAXIS AS HIV PREVENTIVE MEASURES - Baros, Sladjana; Grujicic, Sandra (HEALTH CARE, 2022)
HIV chemoprophylaxis started to be used since the first AIDS drug was registered, i.e. in 1987. Postexposure prophylaxis (PEP), used by persons accidentally exposed to HIV, is mostly related to professional accidental exposure to HIV (mostly among healthcare workers). It is estimated that PEP decreases HIV risk by 81%. Research and implementation of pre-exposure prophylaxis (PrEP) started about 10 years ago. PrEP is intended for use among those who are HIV negative, and in the continuous HIV risk due to their behavior. It is estimated that PrEP use decreases HIV risk by 75% or more, depending on the population and adherence to treatment. In Serbia, PEP and PrEP are still not fully regulated. However, in 2022, the work on regulations has started. In countries with unregulated PrEP, there is a risk from informal therapy use without medical supervision, which can lead to the development of resistant HIV cases among those with previously undiagnosed HIV infection. Both interventions belong to the biomedical HIV preventive interventions, and both are relevant for reaching the global AIDS target – to end AIDS as a “public health threat” by 2030. Nevertheless, for biomedical interventions to be at maximum efficacy, they have to be integrated with adequate behavioral ones, aiming to increase information, adherence to the therapy, and to periodical medical supervision, in line with defined PEP and PrEP recommendations.
Keywords: post-exposure prophylaxis; pre-exposure prophylaxis; HIV infection; AIDS; healthcare workers; biomedical interventions